Industrial Training Report: Tok Kenali Library Institut Pendidikan Guru Campus Kota Bharu Pengkalan Chepa / Nurul Fatin Amira Jafree - Jafree, Nurul Fatin Amira
This report is about information of organization and training activities during my practical training at Tok Kenali library lnstitut Pendidikan Guru Campus Kota Bharu Kelantan from 1st February 2018 until 28 June 2018. This report contain about background, structure, function of organization which is Tok Kenali library. This report also contain about industrial training activities, lessons that learned when at this place and also recommendation to this organization.